Measuring Factors to Increase Village Financial Accountability - Cecilia Lelly Kewo; Lenny Leorina Evinita (Universitas Pasundan, 2024)
The aim of the research is to measure the influence of the accounting system on village financial accountability, test the influence of implementing good governance on village financial accountability, test the influence of internal control on village financial accountability and test the influence of organizational commitment on village financial accountability. This research was carried out using a cross-sectional survey and random sampling and research data was collected from 138 village officials in Minahasa Regency, including village heads, village secretaries and village finance officers. Data collection was carried out using questionnaires given directly or filled out via g-form. The method used in the research is quantitative with partial least squares (PLS) analysis. The research results show that a good accounting system can increase village financial accountability. Likewise, internal control implemented well, and high organizational commitment can increase village financial accountability. However, the results show that the implementation of good governance has not been able to increase financial accountability. This research shows that it is necessary to increase the role of district/sub-district governments in developing, supervising, and increasing community participation in budget preparation, and maximizing the competence of apparatus in managing village finances. These actions are essential for sustainable financial practices.